The Stone Age in Northwestern Libya: Observations Along a Pipeline - Parenti, Fabio; Mengoli, Davide; Natali, Luca (The African Archaeological Review, 2015)
More than 500 km, from the Mediterranean coast to the Hammada al-Hamra, were surveyed in 2002-'03 along the AGIP-Gas pipeline. Several morphological units were crossed: the Jefara, the Jebel Gharbi and the Hammada al-Hamra. This paper reports the location of more than 60 surface sites, with special attention to Lower and Middle Stone Age assemblages, by far the most represented periods. More than 6,500 lithic artifacts have been collected spanning from Mode 1 to the Late Stone Age. The survey was carried out on foot, along a narrow band of around 50 m width for 80 % of the pipeline, representing an extraordinary sample from the coast to the northern desert and, more extensively, in the Wafa area on the Hammada plateau, where stone quarries, fireplaces and important lithic scatters were documented. On the whole, the assemblages, compared with the main Stone Age sites of Northern Africa, seem older in the very southern sector, well into the Hammada, whereas sites on the Jebel cliff and immediately south are dominated by Middle and Late Stone Age cultural traits. The survey proved to be both a good tool for planning development projects and an important occasion for the study of a relevant region of Northern African prehistory. Plus de 500 km du gazoduc AGIP ont été prospectés en 2002-'03, de la côte méditerranéenne jusqu'à la Hammada al-Hamra, sur plusieurs unités morphologiques: Jefara, Jebel Gharbi, Hammada al-Hamra. Cette prospection a permis de décrire plus de 60 gisements de surface, la plupart attribués au Paléolithique inférieur et moyen (phases culturelles le plus fréquemment rencontrées). Plus de 6500 artefacts lithiques ont ainsi été récoltés, de l'Oldowayen au Late Stone Age. La prospection s'est faite à pied, le long d'une bande étroite de 50 m sur 4/5 du parcours, ce qui représente un échantillon extraordinaire, de la côte jusqu'au désert septentrional, et plus en détail dans la région de Wafa, sur le plateau de l'Hammada, où des ateliers de taille, foyers et autres sites de surface ont été trouvés. Les sites sembleraient plus anciens dans la partie méridionale du secteur, bien à l'intérieur de la Hammada. Sur les abords du Jebel, et immédiatement au Sud, les sites du Pleistocène supérieur dominent, Middle et Late Stone Age. Le potentiel archéologique de cette région est analysé dans le cadre de la préhistoire paléolithique nord-africaine.
Keywords: Archéologie – Djebel Nefousa

Libyan-Italian Joint Mission in the Jebel Gharbi (Tripolitania) : the Holocene sequence of the Jifarah plain - Barich, Barbara E.; Lucarini, Giulio; Mutri, Giuseppina (Libya Antiqua, 2015)
Keywords: Archéologie – Djebel Nefousa